DIGITAL DINING INNOVATION: UI/UX DESIGN OF THE REST-O MOBILE APPLICATION USING DESIGN THINKING METHOD (Proceeding of SINERGY, 2026)
The culinary sector plays a significant role in Indonesia’s growing creative economy, driven by changing consumer behavior among Generation Z and Millennials. Despite the increasing preference for dine-in experiences, long waiting times and inefficient reservation processes remain major challenges that negatively affect customer satisfaction. These issues highlight the need for user-centered digital solutions that improve efficiency and convenience in restaurant services. This study aims to design the user interface (UI) and user experience (UX) of Rest-O, a mobile restaurant reservation application developed using the Design Thinking methodology. The research follows five iterative stages: empathize, define, ideate, prototype, and test, enabling the design to be based on real user needs and insights. The proposed application integrates features such as table reservations, pre-arrival menu ordering, and a 360-degree virtual restaurant tour to reduce waiting time and enhance the overall dining experience. Usability evaluation was conducted using the System Usability Scale (SUS) with five participants, resulting in an average score of 88, which falls into the “Excellent” category. These results indicate that the Rest-O UI/UX design is intuitive, efficient, and well-aligned with user expectations. The study concludes that a user-centered design approach can significantly improve service efficiency and user satisfaction in the culinary industry.